(4 root 3 -2 root 2) (3 root 2+4 root 3)

Question

(4 root 3 -2 root 2) (3 root 2+4 root 3)

in progress 0
Ivy 12 hours 2021-11-25T01:36:33+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-25T01:38:30+00:00

    Answer:

    (4 \sqrt{3 }  - 2 \sqrt{2} )(3 \sqrt{2}  + 4 \sqrt{3} ) \\  = (4 \sqrt{3}  \times  3 \sqrt{2} ) + (4 \sqrt{3}  \times 4 \sqrt{3} ) + ( - 2 \sqrt{2}  \times 3 \sqrt{2} ) + ( - 2 \sqrt{2}  \times 4 \sqrt{3} ) \\  = 12 \sqrt{6}  + 48 - 12 - 8 \sqrt{6}  \\  = 4 \sqrt{6}  + 36

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )